Effects of the Openness to Experience Polygenic Score on Cortical Thickness and Functional Connectivity - Ren, Zhiting; Liu, Cheng; Meng, Jie; Liu, Qiang; Shi, Liang; Wu, Xinran; Song, Li; Qiu, Jiang (Frontiers in Neuroscience, 2021)
Openness to experience has relatively stable and heritable characteristics. Previous studies have used candidate gene approaches to explore the genetic mechanisms of openness to experience, but GPSs has a greater genetic effect than other genetic analysis methods, and previous studies have never examined the potential effect of openness to experience on this cumulative effect at the level of the brain mechanism. In this study, we aim to explore the associations between polygenic scores (PGSs) of openness to experience and brain structure and functions. Based on the results of PGSs of openness to experience at seven different thresholds were calculated in a large Chinese sample (N = 586). Then, we determined the associations between openness to experience PGSs and cortical thickness and functional connectivity. The results showed that openness to experience PGSs was negatively correlated with the thickness of the fusiform gyrus, and openness to experience PGSs were negatively associated with the functional connectivity between the left intraparietal sulcus (IPS) and the right posterior occipital lobe. These findings may suggest that the brain structure of fusiform gyrus and brain functions of IPS and posterior occipital lobe are partly regulated by openness to experience-related genetic factors.